THE EFFECT OF SUSTAINABLE LAND MANAGEMENT (SLM) TECHNOLOGIES ON FOOD SECURITY OF FARMING HOUSEHOLDS IN KWARA STATE, NIGERIA. - Salau, Shehu Abdulganiyu (Journal of Agricultural Sciences (Belgrade), 2019)
Nigeria is among countries of the world confronted with food insecurity problem. The agricultural production systems that produces food for the teaming population is not endurable. Attention is thus being given to alternative approaches of intensification such as the use of Sustainable Land Management (SLM) technologies. Thus, this study assessed the effect of SLM technologies on food security of farming households in Kwara State, Nigeria. A-three stage sampling technique was used to select a sample of 200 farming households for this study. Descriptive statistics, Shriar index, likert scale, food security index and logistic regression were employed for the analysis. The result indicated that majority (41%) of the household heads were between the ages of 51 and 70 years with an average of 60.5 years.  Food security index revealed  that 35% and 65% of the households were food secure and food insecure respectively. The logistic regression showed that SLM technologies, estimated income, household size, gender and age of the household heads were the critical determinants of food security among farming households. The most critical coping strategies employed by the respondents in cushioning the effects of food insecurity are reduction in quality of food consumed, engaging in off-farm jobs to increase household income and diversion of money meant for other purposes to buy foods. Governments should encourage the adoption and use of SLM technologies at all levels. Policies and strategies that reduce household size should be enthusiastically pursued to reduce food insecurity.